Evaluating a Driving While Intoxicated (DWI) Night Drug Court in Las Cruces, New Mexico, 1997-1998 - Winfree, L. Thomas ([Verlag nicht ermittelbar], 2001)
The purpose of this study was twofold. First, researchers wanted to assess the benefits of the driving while intoxicated (DWI) drug court established in the Las Cruces, New Mexico, Municipal Court in an effort to determine its future viability. This was accomplished by examining the behaviors and attitudes of three groups of convicted drunk-drivers and determining the extent to which these groups were different or similar. The three groups included: (1) non-alcoholic first- and second-time offenders (non-alcoholic offenders), (2) alcoholic first- and second-time DWI offenders (alcoholic offenders), and (3) chronic three-time (or more) DWI offenders (chronic offenders). The second purpose of this study was to explore police officers' attitudes toward court-based treatment programs for DWI offenders, while examining the distinguishing characteristics between police officers who support court-based programs for drunk drivers and those who are less likely to support such sanctions. Data for Part 1, Drug Court Survey Data, were collected using a survey questionnaire distributed to non-alcoholic, alcoholic, and chronic offenders. Part 1 variables include blood alcohol level, jail time, total number of prior arrests and convictions, the level of support from the respondents' family and friends, and whether the respondent thought DWI was wrong, could cause injury, or could ruin lives. Respondents were also asked whether they acted spontaneously in general, took risks, found trouble exciting, ever assaulted anyone, ever destroyed property, ever extorted money, ever sold or used drugs, thought lying or stealing was OK, ever stole a car, attempted breaking and entering, or had been a victim of extortion. Demographic variables for Part 1 include the age, gender, race, and marital status of each respondent. Data for Part 2, Police Officer Survey Data, were collected using a survey questionnaire designed to capture what police officers knew about the DWI Drug Court, where they learned about it, and what factors accounted for their attitudes toward the program. Variables for Part 2 include police officers' responses to whether DWI court was effective, whether DWI laws were successful, the perceived effect of mandatory jail time versus treatment alone, major problems seen with DWI policies, if DWI was considered dangerous, and how the officer had learned or been briefed about the drug court. Other variables include the number of DWI arrests, and whether respondents believed that reforms weaken police power, that DWI caused more work for them, that citizens have bad attitudes, that the public has too many rights, and that stiffer penalties for DWI offenders were more successful.